The first Russian female soil scientist - V. A. Isaev; M. Yu. Egorova (Бюллетень Почвенного института им. В.В. Докучаева, 2021)
The year 2021 is marked by the 175-th anniversary of the birth of Anna Egorovna and Vasiliy Vasilievich Dokuchaevs. This is a wonderful occasion to recall an amazing and remarkably modest woman who played an important role in the life and work of the great Russian natural scientist, the founder of genetic soil science. If many works were written about her outstanding world-wide known husband, films were made, pictures were created, his photos are preserved, then the life of his wife is undeservingly poorly described, and the appearance of this very beautiful woman is depicted in the only one famous portrait. This article, dedicated to the memory of Anna Egorovna Dokuchaeva, is based on both the quotations from the already published memoirs of the follower and the friend of V.V. Dokuchaev – Franz Yulievich Levinson-Lessing, and the excerpts from Anna Egorovna’s letters to Varvara Ippolitovna – the wife of F.Yu. Levinson-Lessing. These letters were collected from the archives of the Academy of Sciences in St. Petersburg and copied by the employee of the V.V. Dokuchaev Soil Science Institute – Sergey Petrovich Lyalin – in the 1980s, and they are now kindly provided by the Central Soil Museum by V.V. Dokuchaev (the Branch of the Federal Research Centre “V.V. Dokuchaev Soil Science Institute” in St. Petersburg).